Pressure pain threshold, lifestyle, muscle strength and functional capacity in elderly women with sarcopenia - Lima, Alessandra Rodrigues Souto; Portes, Leslie Andrews; Oliveira, Natália Cristina de; Alfieri, Fábio Marcon (Acta Fisiátrica, 2016)
Objective: The present study sought to assess the impact of this condition on muscle strength, functional capacity, lifestyle, and the pressure pain threshold. Methods: Elderly people considered healthy (n = 75) aged 60-75 years (66.8 ± 4.6 years) were studied in an observational and crosssectional design. Those who registered pain above 4 on the Visual Analogue Scale (VAS) and used analgesic and/or anti-inflammatory medication were excluded from the study. Body composition and presence of sarcopenia were evaluated by bioelectric impedance. Two groups were formed: CO - control group (n = 51) and SARC - sarcopenic group (n = 24, muscle mass index less than 6.86 kg/m2 ). Results: Functional capacity was determined by the 6-minute walk test (6MWT); handgrip strength and elbow flexion strength were both determined by dynamometry. Lifestyle was assessed by the FANTASTIC questionnaire. The pressure pain threshold was determined by algometry. Data were analyzed using the Student’s t-test (p < 0.05). CO and SARC did not differ regarding age, body fat percentage, lifestyle, 6MWT, elbow flexion strength, or in algometry measurements at almost any point. However, statistically significant differences between groups were found regarding handgrip strength and algometry in the right insertion of the biceps. Conclusion: Elderly women with significant reduction of muscle mass do not present impairments in functionality or in the sensation of muscle and tendon pain, probably due to a pre-sarcopenic condition